Influence of Social Media to the Buying Behavior on Shopee of Selected BCP College Students: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Social media is playing a different role in our lives. It can be used for communication orconnection with other people around the world since it is the fastest way to reach them. Thisstudy aims to investigate the Influence of Social Media on the Buying Behavior of Shopee ofSelected BCP College Students. From the findings, the researchers create a solution plan asa guide for the enhancement of BCP Bookstore.The results revealed that the majority of the respondents are BSBA students 4th year, with4,000 above monthly allowance, sometimes purchased on Shopee, and Facebook is the mostcommonly used social media platform. When it comes to the influence of social media, bothworking and full-time students strongly agree that information, product reviews, and legitimacyare highly recommended when searching for desirable products. There is a significantdifference between working and full-time students in assessing the cited variables. The mostencountered challenge by the consumers of Shopee is customers experiencing delayedorders.From the results, the following recommendations are as follows: Shopee users must buy aproduct that fits their income, that is useful, and for personal needs; consumers must becareful and wise about what they see and hear on social media and do deep research on atrend before going for it, sellers should consider offering their products for men and womendifferently, Shopee must improve service quality and customer service. Consumers also needto track their orders and have prior knowledge of how to handle the issues that may beencountered, and the proposed solution in the study may be used by the seller as a guide toaddress some issue and problems that really happens in online selling.
Keywords: Business